(untitled) (Architecture Image Studies, 2025)
This study aims to analyze and examine the influence of e-service quality, e-trust, and bank image on customer loyalty, mediated by e-satisfaction among Muamalat DIN users at PT Bank Muamalat Indonesia, Kendari Branch. The research was conducted within the scope of PT Bank Muamalat Indonesia, Kendari Branch, involving 154 electronic banking customers as research respondents. Data were collected using an online questionnaire distributed to the respondents. The collected data were then analyzed using descriptive analysis and SEM PLS 4. The results of the study indicate that e-service quality has an insignificant effect on e-loyalty. E-trust also has an insignificant effect on e-loyalty. Bank image has a negative yet insignificant effect on e-loyalty. E-satisfaction has a positive and significant effect on e-loyalty. E-service quality has a positive and significant effect on e-satisfaction. E-trust has a positive and significant effect on e-satisfaction. Bank image has a positive and significant effect on e-satisfaction. E-satisfaction does not significantly mediate the effect of e-service quality on e-loyalty. E-satisfaction significantly mediates the effect of e-trust on e-loyalty with full mediation. E-satisfaction also significantly mediates the effect of bank image on e-loyalty with full mediation.